Prinsip Dan Fungsi Manajemen Pendidikan Dalam Perspektif Islam - M Ihsan Al Fikri; Fadhilah Fadhilah Fadhilah; Asmendri Asmendri Asmendri; Milya Sari (LPPM Universitas Muhammadiyah Sumatera Barat, 2025)
This article aims to comprehensively examine the principles and functions of educational management in the Islamic perspective by exploring the synthesis between classical management theories and Islamic normative values. The study assumes that the effectiveness of Islamic educational institutions is not solely determined by rational resource management but also by the integration of spiritual, ethical, and social values derived from the Qur’an and Sunnah. Using a qualitative library research approach, the study reviews management concepts from key theorists such as Henri Fayol, G.R. Terry, Harold Koontz, and Sondang P. Siagian, and connects them to Islamic principles such as tawheed, sincerity, trust, justice, and consultation. The findings show that Islamic educational management principles and functions form a leadership model balancing efficiency and worship values, performance and morality. This integration creates an educational management paradigm that is professional, effective, and oriented toward social welfare and holistic human development.